Effects of plyometric training on lower and upper extremity power in karate practitioners - Nowakowska, M.; Zaton, M.; Wierzbicka-Damska, I. (Journal of Combat Sports and Martial Arts, 2017)
Introduction. It has been suggested that the performance characteristics of competitive karate formats (intermittent high-intensity activity of brief duration with short recovery periods) involve a large anaerobic component. Hence, performance and effectiveness may be improved by enhancing anaerobic power and capacity. The aim of this study was to investigate the effects of an 8-week plyometric-based intervention in adolescent karate practitioners. Material and methods. Nineteen male karate practitioners were divided into an experimental and control group. The control group performed traditional karate training (four sessions per week). Training in the experimental group was amended to include plyometric-based exercises targeting the lower and upper body but maintained the same training volume as the control group (four sessions per week). Pre- and post-intervention anaerobic performance was measured by calculating peak power (PP) and the time to reach PP (tPP) in a 10-s variation of the Wingate Anaerobic Test separately for the upper and lower extremities. Results. PP and tPP magnitudes significantly increased in the experimental group and the between-group differences at post-intervention were also significant. Conclusions. The introduction of plyometric exercises in a traditional karate training protocol can significantly increase upper- and lower-extremity anaerobic performance.